Higher expectations : can colleges teach students what they need to know in the twenty-first century? - Bok, Derek Curtis (Princeton, N.J. : Princeton University Press, 2020)
"Over its long history, undergraduate education has gradually evolved from its early years when colleges offered an exacting study of classical texts to the tiny segment of America's young men destined for careers as ministers, teachers, and civic leaders. After the United States began to industrialize during the 19th century, the demand for graduates with practical skills led eventually to the demise of the classical curriculum to make way for more useful and contemporary subjects. As the Gross Domestic Product grew rapidly in the decades following World War II, the need for competent managers and professionals grew with it. In response, the size and variety of vocational programs exploded to accommodate an enormous growth in the number of young men and women seeking to enroll. Today, the undergraduate curriculum may be entering a new phase. The needs of an increasingly sophisticated economy coupled with advances in the cognitive sciences have given rise to intriguing possibilities for helping students to acquire additional competencies and qualities of mind that could enable them to live more successful, useful, and satisfying lives. This book asks a straightforward question: Do colleges and universities have the right curricula and pedagogy to prepare today's students for the future? Former Harvard president Derek Bok examines this question according to the following measures: Preparation for Citizenship; Preparing Students for an Interdependent World; Character; A Purposeful and Meaningful Life; Improving Interpersonal Skills; and Improving Intrapersonal Skills. He then explores Unconventional Methods of Teaching; Prospects for Change; and Reform; and concludes with Reflections on the Future"--
Introduction : an overview -- A brief history of the college curriculum from 1636 to the present -- Educating citizens -- Preparing students for an interdependent world -- Character : can colleges help students acquire higher standards of ethical behavior and personal responsibility? -- Helping students find a purposeful and meaningful life -- Improving interpersonal skills -- Improving intra-personal skills -- Unconventional methods of teaching -- Prospects for change -- Encouraging reform -- Conclusion : reflections on the future.
Includes bibliographical references and index.
Keywords: Education, Higher -- Aims and objectives -- United States; Education, Higher -- Curricula -- United States; College teaching -- United States; Educational change -- United States; Education and globalization